2014
DOI: 10.1167/iovs.13-13030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posture-Induced Intraocular Pressure Changes in Medically Treated and Surgically Treated Eyes With Open-Angle Glaucoma

Abstract: The lower posture-induced IOP change in the successfully trabeculectomized eyes indicates that trabeculectomy will not only lead to a decrease in the IOP but also lower the posture-induced IOP change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…It has also been reported that eyes with glaucoma that had undergone trabeculectomy showed less diurnal IOP fluctuation than eyes with medically treated glaucoma [ 27 , 28 ] and that trabeculectomy reduced the degree of posture-induced IOP changes in OAG. [ 29 33 ] Sawada et al [ 31 ] reported that eyes with successfully trabeculectomized OAG showed smaller posture-induced IOP changes than eyes with non-operated, medically treated OAG, despite the mean IOP in both groups being the same (9.7 mmHg). Given that trabeculectomy creates a new aqueous pathway via the filtering bleb that is independent of the episcleral veins, it seems reasonable that the surgery could cause suppression of posture-induced IOP alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that eyes with glaucoma that had undergone trabeculectomy showed less diurnal IOP fluctuation than eyes with medically treated glaucoma [ 27 , 28 ] and that trabeculectomy reduced the degree of posture-induced IOP changes in OAG. [ 29 33 ] Sawada et al [ 31 ] reported that eyes with successfully trabeculectomized OAG showed smaller posture-induced IOP changes than eyes with non-operated, medically treated OAG, despite the mean IOP in both groups being the same (9.7 mmHg). Given that trabeculectomy creates a new aqueous pathway via the filtering bleb that is independent of the episcleral veins, it seems reasonable that the surgery could cause suppression of posture-induced IOP alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating postural IOP changes have primarily focused on open-angle glaucoma 5,7,1012 , whereas few have examined postural IOP changes in PACG patients. Sawada and Yamamoto 13 compared OAG and PAC eyes and reported no correlation between postural IOP change and axial length.…”
Section: Discussionmentioning
confidence: 99%
“…Dies wirkt sich direkt auf die therapeutischen Strategien in der Glaukombehandlung aus. Liegendspitzenerscheinendurcheine medikamentös topische Drucksenkung schlecht adressierbar [55]. Auch nach Kataraktoperation wurde zwar eine Reduktion des IOD im Sitzen, nicht jedoch des lageabhängigen Druckanstiegs nachgewiesen [56].…”
Section: Therapeutische Strategienunclassified
“…Auch nach Kataraktoperation wurde zwar eine Reduktion des IOD im Sitzen, nicht jedoch des lageabhängigen Druckanstiegs nachgewiesen [56]. Bei Erkrankungsprogression und signi-fikanten IOD-Spitzen im Liegen sollte die Indikation zur filtrierenden Glaukomchirurgie erwogen werden [55]. Als Grund für die Überlegenheit der filtrierenden Verfahren zur Therapie von Liegendspitzen kann vermutet werden, dass nur bei der Ableitung des Kammerwassers unter die Bindehaut der venöse Widerstand der episkleralen Venen ausgeschaltet wird.…”
Section: Therapeutische Strategienunclassified